Passivity-based event-triggered fault tolerant control for VTOL with actuator failure and parameter uncertainties - Wang, Xudong; Fei, Zhongyang; Yu, Jinyong; Du, Zhiwei (International journal of systems science, 2019)
This paper investigates passivity based fault tolerant control (FTC) for Vertical Take-off and Landing aircraft system subject to actuator failure under event-driven transmission mechanism. Firstly, a polytopic model is proposed to describe the aircraft dynamics with parameter uncertainties, which is more general in practice. In order to process the lose efficacy of actuator, the failure of actuator is modelled as multiplicative fault model. In addition, the hybrid event trigger transmission mechanism is introduced in FTC to save communication resource. The proposed design method not only ensures the closed-loop system is strictly passive with a prescribed passivity performance index, but also gets rid of Zeno phenomenon fundamentally, which may exist in continuous event trigger scheme. Finally, simulation results are presented to show the validity and application of the proposed method.